Pigouvian Income Taxation - Lassi Ahlvik; Matti Liski; Mikael Mäkimattila (CESifo GmbH, 2024)
This paper develops a mechanism design approach to study externalities and re-distribution. The mechanism screens individuals' social weights to strike a balance among broad distributional objectives, incentives to work, and incentives to reduce externalities. The welfare-optimal allocation can be decentralized through income taxation, defining income-dependent externality payments. Two applications use individual-level administrative data on incomes, pollution measures, and financial burdens to demonstrate how population characteristics shape the optimal policy on carbon emissions.
Keywords: D82; H21; H23; Q54; Q58; 330; Pigouvian taxation; optimal income taxation; inequality; climate change